Construction, characteristics and high throughput molecular screening methodologies in some special breeding populations: a horticultural perspective - ÖZYİĞİT, İBRAHİM İLKER (INDIAN ACAD SCIENCES, 2019)
Advanced marker technologies are widely used for evaluation of genetic diversity in cultivated crops, wild ancestors, landraces or any special plant genotypes. Developing agricultural cultivars requires the following steps: (i) determining desired characteristics to be improved, (ii) screening genetic resources to help find a superior cultivar, (iii) intercrossing selected individuals, (iv) generating genetically hybrid populations and screening them for agro-morphological or molecular traits, (v) evaluating the superior cultivar candidates, (vi) testing field performance at different locations, and (vii) certifying. In the cultivar development process valuable genes can be identified by creating special biparental or multiparental populations and analysing their association using suitable markers in given populations. These special populations and advanced marker technologies give us a deeper knowledge about the inherited agronomic characteristics. Unaffected by the changing environmental conditions, these provide a higher understanding of genome dynamics in plants. The last decade witnessed new applications for advanced molecular techniques in the area of breeding, with low costs per sample. These, especially, include next-generation sequencing technologies like reduced representation genome sequencing (genotyping by sequencing, restriction site-associated DNA). These enabled researchers to develop new markers, such as simple sequence repeat and single- nucleotide polymorphism, for expanding the qualitative and quantitative information on population dynamics. Thus, the knowledge acquired from novel technologies is a valuable asset for the breeding process and to better understand the population dynamics, their properties, and analysis methods.
Keywords: population; backcross; double haploid; recombinant inbred line; near-isogenic line; nested association mapping; multiparent advanced generation intercross; QUANTITATIVE TRAIT LOCI; GENOME-WIDE ASSOCIATION; DOUBLED HAPLOID POPULATION; EGGPLANT SOLANUM-MELONGENA; MARKER-ASSISTED SELECTION; FLOWERING CHINESE-CABBAGE; CROSS MAGIC POPULATION; GENETIC-LINKAGE MAP; YELLOW MOSAIC-VIRUS; DISEASE RESISTANCE